Demonstrating the influence of HTA: INAHTA member stories of HTA impact. (5th November 2020) - Werkö, Sophie Söderholm; Merlin, Tracy; Lambert, Laurie Jean; Fennessy, Paul; Galán, Ana Pérez; Schuller, Tara
Abstract: A central function of health technology assessment (HTA) agencies is the production of HTA reports to support evidence-informed policy and decision making. HTA agencies are interested in understanding the mechanisms of HTA impact, which can be understood as the influence or impact of HTA report findings on decision making at various levels of the health system. The members of the International Network of Agencies for HTA (INAHTA) meet at their annual Congress where impact story sharing is one important activity. This paper summarizes four stories of HTA impact that were finalists for the David Hailey Award for Best Impact Story . The methods to measure impact include: document review; claims analysis and review of reimbursement status; citation analysis; qualitative evaluation of stakeholders' views; and review of media response. HTA agency staff also observed changes in government activities and priorities based on the HTA. Impact assessment can provide information to improve the HTA process, for example, the value of patient and clinician engagement in the HTA process to better define the assessment question and literature reviews in a more holistic and balanced way. HTA reports produced by publicly funded HTA agencies are valued by health systems around the globe as they support decision making regarding the appropriate use, pricing, reimbursement, and disinvestment of health technologies. HTAs can also have a positive impact on information sharing between different levels of government and across stakeholder groups. These stories show how HTA can have a significant impact, irrespective of the health system and health technology being assessed.